Analysis of 7th Grade Junior High School Students Learning Interest on Social Arithmetic Using Liveworksheets - Nurfalah, Ilma; Amelia, Risma ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
The aim of this research was to find out about the learning interests of junior high school students in learning social arithmetic after learning using liveworksheets. In this study using a qualitative descriptive research method, the research subjects were 7th grade junior high school students at SMPN 14 Cimahi. The sample used in this study was 30 students. The research instrument used was an interest in learning mathematics scale questionnaire referring to 4 indicators containing 20 statements according to the indicators of interest in learning with a large number of statements totaling 12 positive statements and 8 negative statements. The implementation of distributing questionnaires is a data collection techniques in this study. Data processing techniques with reference to the results of student answers are described using the criteria for the percentage of interest in learning. The indicators of interest in learning are as follows (1) feeling happy, (2) student interest, (3) student engagement, and (4) indicate attention while studying. The findings obtained from analyzing this study indicate that the average student interest in learning is 80,5% with very good criteria, so the use of liveworksheets is proven to be very helpful for students in building their interest in learning in social arithmetic learning.